Sonochemical Synthesis and Characterization of Rod-Shaped Bi2O3/ZnO Anchored with f-MWCNT Nanocomposite for the Electrochemical Determination of Ofloxacin. Issue 8 (5th August 2021) - Manjula, Natesan; Chen, Tse-Wei; Chen, Shen-Ming; Lou, Bih-Show
Abstract : Detection of trace quantities of pharmaceutical drug ofloxacin (OFL) must be very simple and accurate. Innovative honeycomb-like structures have received considerable attention over the years due to their superior electrochemical and mechanical character. Herein, rod-shaped Bi2 O3 /ZnO and multiwalled carbon nanotubes were assembled to form a honeycomb structure like nanocomposite (hc-Bi2 O3 /ZnO:f-MWCNT). The new hc-BZM was synthesized via the cost-effective sonochemical method. A simple and convenient electrochemical determination of OFL was developed based on hc-BZM modified GCE. The physicochemical and electrochemical characterization was investigated by CV and DPV. The respective calibration curve has good linearity with current vs the concentration of OFL in the range of 0.5 to 39 μ M with a correlation coefficient of R 2 = 0.991. From the calibration curve slope, the detection limit and sensitivity were determined to be 0.03 μ M and 1.063 μ A μ M –1 cm –2 . The proposed sensor explained the structural advantages of simple design, low cost, wide linear range, good selectivity, and reusability. Also, the suggested hc-BZM composites can provide a new platform for the simultaneous determination of OFL, PXM, and DA. Finally, the sensor was successfully applied for the determination of OFL in human urine and serum sample, the obtained results have good agreement with added and the recovery value.